HUBUNGAN MINAT BELAJAR DENGAN KEBUGARAN JASMANI SISWA PROGRAM KELAS KHUSUS OLAHRAGA DI SMP MUHAMMADIYAH 5 SURAKARTA - Rafi Haristiarto, Imanda; Sudarmanto, Eko; Septi Sistiasih, Vera; Jariono, Gatot (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The Special Sports Class program is designed to facilitate students with interest and talent in sports so that they can develop optimally. However, a high level of learning interest does not necessarily correspond to students’ physical fitness. This study aimed to analyze the relationship between learning interest and physical fitness among students enrolled in the special sports class program at SMP Muhammadiyah 5 Surakarta. This quantitative study employed a correlational design. The sample was selected using purposive sampling and consisted of 30 volleyball-specialized students. Learning interest was measured using a questionnaire, while physical fitness was assessed using the Indonesian Student Fitness Test (TesKebugaran Pelajar Nusantara/TKPN). The Shapiro-Wilk normality test showed that learning interest scores were normally distributed (p = 0.131), whereas physical fitness scores were not normally distributed (p < 0.001). Therefore, the relationship between variables was analyzed using Spearman’s rank correlation. The results showed a Spearman correlation coefficient of rho = 0.074 with a significance value of p = 0.699. These findings indicate that there is no significant relationship between learning interest and physical fitness among special sports class students. Thus, improving students’ physical fitness requires more than enhancing learning interest; it should be supported by structured physical conditioning, nutritional status monitoring, sedentary behavior control, and continuous healthy lifestyle development.